Pengaruh Komunikasi, Kepemimpinan dan Insentif Terhadap Kinerja Karyawan Pada PT. Jaya Anugrah Sukses Abadi - Cindy Marceline; Demak Claudia Yosephine Simanjuntak; Claudia Lorenza; Albert Albert (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The importance of Human Resources needs to be realized by every level of management in the company, in order to improve the company's development. This research was conducted by researchers with the aim of testing and analyzing the influence of communication, leadership and incentives on employee performance at PT. Jaya Anugrah Sukses Abadi. In this study, the method used in this study is multiple linear regression analysis. Where the total population amounted to 176 consumers and the number of samples in this study amounted to 122 consumers. From the results of this study conducted by researchers, it was found that partially and simultaneously the quality of communication, leadership and incentives had a positive and significant effect on employee performance at PT. Jaya Anugrah Sukses Abadi. The coefficient of determination is 0.653 which means 65.3% of employee performance which can be explained by communication, leadership and incentives, while the remaining 34.7% is explained by other variables not examined in this study. Keywords: Incentives; Leadership; Employee performance; Communication.